Cranial morphology and influence on the quality of breastfeeding and sucking in infants (Research, Society and Development, 2023)
Congenital malformations in sutures are changes known as craniosynostosis, where the premature union of one or more cranial sutures occurs, which can lead to deformities in the skull in different degrees and proportions. To measure cranial dysfunctions, the assessment consists of a device, the manual craniometer. The objective of this study is to verify whether there is a relationship between cranial morphology and the quality of breastfeeding of newborns in the maternal and child unit of the Hospital Universitário do Oeste do Paraná. Newborns were evaluated between 24 and 48 hours, where an interview was carried out with the mother and subsequently LATCH assessment and craniometry of the newborns, in order to determine the quality of breastfeeding and cranial morphology. 82 newborns participated in the study, of which 51 were excluded. The sample for the study was 31 newborns, 18 (58.06%) of whom were male, with an average weight of 3.224kg and length of 48.80cm. The average age of the mothers was 26 years and the gestational age was 39 weeks. The predominant type of birth was cesarean section with 19 (61.29%). Given the data obtained, it is concluded that regardless of whether the CVAI is normal or altered and/or the LATCH is normal or altered, there is no correlation of dependence with statistical significance and there may be no correlation in the change with the quality of breastfeeding and sucking in patients infants in the first 24 to 48 hours of life for this specific group.